2019
DOI: 10.1039/c9cc06446j
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium catalyzed C–C bond cleavage/coupling of 2-(azetidin-3-ylidene)acetates and analogs

Abstract: The tandem “conjugate addition/β-C cleavage/protonation” process (CCP) is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…In the 1950s, heterolytic fragmentations were considered to be advanced methods for cleaving C­(sp 3 )–C­(sp 3 ) bonds . Until now, C–C bond cleavage reaction has made great achievements by the groups of Song and Jiao, Xu, Kakiuchi, Wei, Ouyang and Xie, Han, Hyodo, Xiao and Zhou, our work, and others . For example, in 2017, Song and Jiao et al reported an allylic C–C bond cleavage reaction of olefins to synthesis of cinnamyl aldehydes in the presence of alkyl azides, DDQ, and TFA .…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In the 1950s, heterolytic fragmentations were considered to be advanced methods for cleaving C­(sp 3 )–C­(sp 3 ) bonds . Until now, C–C bond cleavage reaction has made great achievements by the groups of Song and Jiao, Xu, Kakiuchi, Wei, Ouyang and Xie, Han, Hyodo, Xiao and Zhou, our work, and others . For example, in 2017, Song and Jiao et al reported an allylic C–C bond cleavage reaction of olefins to synthesis of cinnamyl aldehydes in the presence of alkyl azides, DDQ, and TFA .…”
mentioning
confidence: 84%
“…3 In the 1950s, heterolytic fragmentations were considered to be advanced methods for cleaving C(sp 3 )− C(sp 3 ) bonds. 4 Until now, C−C bond cleavage reaction has made great achievements by the groups of Song and Jiao, 5 Xu, 6 Kakiuchi, 7 Wei, 8 Ouyang and Xie, 9 Han, 10 Hyodo, 11 Xiao and Zhou, 12 our work, 13 and others. 14 12 The fused chromeno quinolines have shown important roles in biological, medicinal, and fluorescence areas (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Selective carbon–carbon bond (C–C) cleavage reactions have been utilized as powerful tools for the installation of functional groups and new connections. , Typically, C–C cleavage is achieved by β-scission of radicals or cleavage of strained rings. Since most of these cleavage reactions need transition metals as catalysts , and harsh reaction conditions, selective cleavage of unstrained C–C bonds at ambient conditions without using transition metal catalysts remains as a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Typically, C−C cleavage is achieved by β-scission of radicals 3−6 or cleavage of strained rings. 7−10 Since most of these cleavage reactions need transition metals as catalysts 11,12 and harsh reaction conditions, selective cleavage of unstrained C−C bonds at ambient conditions without using transition metal catalysts remains as a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%